2013
DOI: 10.1063/1.4826609
|View full text |Cite
|
Sign up to set email alerts
|

The influence of inertia and charge relaxation on electrohydrodynamic drop deformation

Abstract: We quantify the transient deformation of a droplet immersed in a weakly conductive (leaky dielectric) fluid upon exposure to a uniform DC electric field. Capillary forces are assumed to be sufficiently large that the drop only slightly deviates from its equilibrium spherical shape. In particular, we account for transient (or linear) fluid inertia via the unsteady Stokes equations, and also account for a finite electrical relaxation time over which the drop interface charges. The temporal droplet deformation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…We summarize here the results of the theory and outline the solution procedure at first and second order. We also compare and contrast our predictions with the existing theories of Taylor (1966), Ajayi (1978), Esmaeeli & Sharifi (2011) and Lanauze et al (2013).…”
Section: Summary Of the Small-deformation Theorymentioning
confidence: 88%
See 2 more Smart Citations
“…We summarize here the results of the theory and outline the solution procedure at first and second order. We also compare and contrast our predictions with the existing theories of Taylor (1966), Ajayi (1978), Esmaeeli & Sharifi (2011) and Lanauze et al (2013).…”
Section: Summary Of the Small-deformation Theorymentioning
confidence: 88%
“…Accordingly, it satisfies the conservation equation oblate shapes, suggesting an inconsistency in the model. This discrepancy was recently resolved by Lanauze et al (2013), who showed using a small-deformation theory that either transient charge relaxation or fluid acceleration, combined with transient shape deformations, needs to be included in the model to capture the correct behavior.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient deformation of a leaky dielectric drop has also received theoretical (Esmaeeli & Sharifi 2011;Lanauze, Walker & Khair 2013;Zhang, Zahn & Lin 2013) and computational (Supeene et al 2008;Halim & Esmaeeli 2013) treatment. For such low-conductivity systems, the finite amount of time taken for a quantity of charge q * to arrive at the interface, characterized by the charge relaxation time scales τ e(i,o) , implies that another form of charge transport must be accounted for: the interfacial accumulation of charge.…”
mentioning
confidence: 98%
“…Supeene et al (2008) implemented the finite-element method to predict the transient deformation of a leaky dielectric drop via a general electrokinetic model and a surface charge conservation equation. Lanauze et al (2013) developed an O(Ca) perturbation theory that accounts for charge relaxation and linear inertia. These computational and theoretical efforts have predicted prolate-oblate shape transitions at intermediate times for ultimately steady oblate conformations due to the dominance of the charge relaxation time scales τ e(i,o) (i.e.…”
mentioning
confidence: 99%